2009
DOI: 10.5194/ars-7-5-2009
|View full text |Cite
|
Sign up to set email alerts
|

Considerations on radar localization in multi-target environments

Abstract: Abstract. In a multitude of applications like e.g. in automotive radar systems a localization of multiple passive targets in the observed area is necessary. This contribution presents a robust approach based on trilateration to detect point scatterers in a two-dimensional plane using the reflection and transmission information of only two antennas. The proposed algorithm can identify and remove ambiguities in target detection which unavoidably occur in certain target constellations in such a two-antenna config… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Geometrically, ghost objects can appear in lateration networks, which represents a wrong data association of the sensor's object lists. A precise derivation, how ghost objects appear, is given by Rabe et al [6].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Geometrically, ghost objects can appear in lateration networks, which represents a wrong data association of the sensor's object lists. A precise derivation, how ghost objects appear, is given by Rabe et al [6].…”
Section: Methodsmentioning
confidence: 99%
“…The range measurement accuracy is defined by the root-mean-square (rms) measurement error [10, p. 167]. According to (6), the range measurement error is formed of the root-sum-square of three error components. The dominating component is the S/N-dependent random range measurement error RN .…”
Section: Considerations On Erroneous Influences On Position Estimatiomentioning
confidence: 99%
“…This approach is an alternative to equation (12) or (13) and does not need any adjustment of tolerances to obtain full accuracy [Fölster and Rohling, 2005;Rabe et al, 2009;Huang and Narayanan, 2014]. Specialized minimization methods [Press et al, 1989] are optional since the minima are easy to find, as shown in Figure 4.…”
Section: 1002/2016rs005974mentioning
confidence: 99%
“…One could combine monostatic and bistatic radar and obtain the target position with only two platforms [ Rabe et al , ], but the problem with the strong eigenecho is then unavoidable.…”
Section: Target Location At Low Frequencies Using Three Platformsmentioning
confidence: 99%
See 1 more Smart Citation